Heuristic Evaluation: Comparing Generic and Specific Usability Heuristics for Identification of Usability Problems in a Living Museum Mobile Guide App - Mohd Kamal Othman; Muhd Nur Shaful Sulaiman; Shaziti Aman (Advances in Human-Computer Interaction)
This paper reports on an empirical study that compares two sets of heuristics, Nielsen’s heuristics and the SMART heuristics in the identification of usability problems in a mobile guide smartphone app for a living museum. Five experts used the severity rating scales to identify and determine the severity of the usability issues based on the two sets of usability heuristics. The study found that Nielsen’s heuristics set is too general to detect usability problems in a mobile application compared to SMART heuristics which focuses on the smartphone application in the product development lifecycle instead of the generic Nielsen’s heuristics which focuses on a wide range of interactive system. The study highlights the importance of utilizing domain specific usability heuristics in the evaluation process. This ensures that relevant usability issues were successfully identified which could then be given immediate attention to ensure optimal user experience.